In-vitro stress stability, digestibility and bioaccessibility of curcumin-loaded polymeric nanocapsules. Issue 1 (15th December 2021) - Abbas, Shabbar; Chang, Dawei; Riaz, Naveeda; Maan, Abid Aslam; Khan, Muhammad Kashif Iqbal; Ahmad, Ishtiaque; Alsagaby, Suliman A.; El-Ghorab, Ahmed; Ali, Mazhar; Imran, Muhammad; Ullah, Azmat; Mehmood, Tahir; et al.
Abstract: Nanoemulsion-based delivery systems have a considerable potential for the encapsulation, protection and delivery of lipophilic bioactives. In the current study, in-vitro stability of curcumin-loaded single (NEI), double (NEII), and triple-layered nanostructures was investigated against varying environmental stress (temperature, pH, ionic strength) and storage conditions. In addition, their functional performance, as influenced by the number of polymer layers, was also assessed by comparing in-vitro lipid digestibility and curcumin bioaccessibility. Initially, NEI was prepared through ultrasonic homogenisation technique, and stabilised with modified starch. Next, sequential deposition of chitosan and carboxymethyl cellulose (CMC) on the NEI droplets resulted into the formation of NEII and nanocapsules, respectively. Nanocapsules showed good stability against aggregation over a wide range of pH (3.0–7.0), salt concentration (50–300 mM NaCl) and temperature (30–90 °C for 30 min). Digestion studies suggested that polymeric coatings interfered with lipolysis as the digestibility (% free fatty acid released) of oil droplets was considerably reduced with increasing the number of layers surrounding the oil droplets. However, curcumin bioaccessibility increased with adding the number of coating layers. Overall, results indicate that the developed nano-system could be helpful in improving the oral delivery of curcumin besides incorporating it into functional foods and beverages.